Class, Gender, and Power in the Mining Communities of the Americas - Mercier, Laurie (Labour / Le Travail, 1999)
The article reviews and comments extensively on Elizabeth Jameson's 'All That Glitters: Class, Conflict, and Community in Cripple Creek' (1998) and Janet L. Finn's 'Tracing the Veins: Copper, Culture, and Community from Butte to Chuquicamata' (1998).
Keywords: 1800-1999; CANADA -- Economic conditions; History; Social conditions; Wales